Post-traumatic hypoxia exacerbates neurological deficit, neuroinflammation and cerebral metabolism in rats with diffuse traumatic brain injury - Yan, Edwin B (BioMed Central, 2011)
BACKGROUND: The combination of diffuse brain injury with a hypoxic insult is associated with poor outcomes in patients with traumatic brain injury. In this study, we investigated the impact of post-traumatic hypoxia in amplifying secondary brain damage using a rat model of diffuse traumatic axonal injury (TAI). Rats were examined for behavioral and sensorimotor deficits, increased brain production of inflammatory cytokines, formation of cerebral edema, changes in brain metabolism and enlargement of the lateral ventricles. METHODS: Adult male Sprague-Dawley rats were subjected to diffuse TAI using the Marmarou impact-acceleration model. Subsequently, rats underwent a 30-minute period of hypoxic (12% O(2)/88% N(2)) or normoxic (22% O(2)/78% N(2)) ventilation. Hypoxia-only and sham surgery groups (without TAI) received 30 minutes of hypoxic or normoxic ventilation, respectively. The parameters examined included: 1) behavioural and sensorimotor deficit using the Rotarod, beam walk and adhesive tape removal tests, and voluntary open field exploration behavior; 2) formation of cerebral edema by the wet-dry tissue weight ratio method; 3) enlargement of the lateral ventricles; 4) production of inflammatory cytokines; and 5) real-time brain metabolite changes as assessed by microdialysis technique. RESULTS: TAI rats showed significant deficits in sensorimotor function, and developed substantial edema and ventricular enlargement when compared to shams. The additional hypoxic insult significantly exacerbated behavioural deficits and the cortical production of the pro-inflammatory cytokines IL-6, IL-1β and TNF but did not further enhance edema. TAI and particularly TAI+Hx rats experienced a substantial metabolic depression with respect to glucose, lactate, and glutamate levels. CONCLUSION: Altogether, aggravated behavioural deficits observed in rats with diffuse TAI combined with hypoxia may be induced by enhanced neuroinflammation, and a prolonged period of metabolic dysfunction.